Clinically Verified Materia Medica: An Explanation and Remedy Example - Morrison, Roger; Herrick, Nancy (Homœopathic Links, 2018)
The ‘Clinically Verified Materia Medica’ is a work in progress. It is based on cured cases only rather than the opinions of the author or other trusted authorities. Only remedies of which at least three well-documented cured cases could be found are included. The basis for this project is a trove of seven to eight thousand cured cases from the practice of Roger Morrison and colleagues as also from journals and e-journals. In this article, a case of Lac lupinum by Nancy Herrick is presented as an example.
Keywords: Clinically Verified Materia Medica; Cured cases; Lac lupinum